ENVIRONMENTAL AND LEISURE ASPECTS OF THE MUNICIPAL LAKE OF ESPÍRITO SANTO DO PINHAL-SP AND THE FAVORING OF THE QUALITY OF LIFE OF THE POPULATION - Martelli, Anderson (Journal of Interdisciplinary Debates, 2022)
Nowadays, urban planning in Brazilian municipalities has sought innovative practices and reflections related to green areas located in urban centers, being an indicator of environmental quality in cities due to the numerous ecological, aesthetic and leisure functions that it can perform. Thus, the objective of this work was to carry out a survey of the environmental and leisure aspects of a green area located in the municipality of Espirito Santo do Pinhal-SP called Municipal Lake used by the population. To carry out this work, the area was covered, portraying the characteristics of the vegetation found in this place and its functions, the water reservoir, the buildings and the use of the place by the citizens regarding the practice of physical exercises. The results showed that the Municipal Lake is located in a privileged area of the municipality, with a considerable number of tree species from the Atlantic Forest biome, among them the araucaria, a symbol tree of this municipality. The space has a water reservoir with a water surface of approximately 28,580m², thus, the arboreal vegetation and this lake favor a local microclimate and the space has a walking track and cycle lane being the place used for sports, leisure together to children and social integration factors that stimulate a quality of life in urban centers.